Service user and carer experiences of the advanced nurse practitioner role in a memory assessment team. (10th September 2020) - Greenbank, Karen; Hemingway, Steve; Thiyagesh, Subha; Stephenson, John
Abstract : Background: Advanced nurse practitioners (ANPs) within memory services can support prompt diagnoses of dementia. Further understanding of the role is necessary as evidence on its effectiveness is limited. Aim: To assess service user and carer satisfaction with the ANP role within Kirklees memory assessment team. Methods: A cross-sectional survey was undertaken to evaluate carer and patient perceptions of the ANP role in a local memory assessment team. The survey was developed using the Royal College of Nursing's four pillars as a structure: clinical/direct care practice, leadership and collaborative practice, improving quality and developing practice, and developing self and others. Results: One hundred and fifteen surveys were sent out, and 85 were completed, a response rate of 73.9%. Patients expressed significant satisfaction with the ANP, in particular in the areas of direct clinical practice (84%) and quality of care received (87%). Conclusion: Patients and families are highly satisfied with the service provided by the ANP. High-quality research is needed on the cost effectiveness and outcomes of ANP interventions.